2010
DOI: 10.1038/hr.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

Rationale and design of the Eplerenone combination Versus conventional Agents to Lower blood pressure on Urinary Antialbuminuric Treatment Effect (EVALUATE) trial: a double-blinded randomized placebo-controlled trial to evaluate the antialbuminuric effects of an aldosterone blocker in hypertensive patients with albuminuria

Abstract: on behalf of the EVALUATE Study InvestigatorsAlthough inhibitors of the renin-angiotensin system are effective as first-line antihypertensive drugs in hypertensive patients with chronic kidney disease, they cannot completely prevent the progression of renal injury. Many animal studies, including our own, and a few human studies suggest that mineralocorticoid receptor blockade could inhibit the ongoing renal damage in chronic kidney disease. Thus, we designed this double-blinded, randomized, placebo-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 34 publications
0
7
1
1
Order By: Relevance
“…While it is increasingly noted that aldosterone mediates cardiac fibrosis (1,2,14), in the current study, there is no activation of aldosterone at 4 wk, which is, however, elevated at 16 wk. Other possible mechanisms that may contribute to the early fibrosis observed in this study can be related to the TGF-␤ and apoptosis pathways (17,27).…”
Section: Discussioncontrasting
confidence: 71%
“…While it is increasingly noted that aldosterone mediates cardiac fibrosis (1,2,14), in the current study, there is no activation of aldosterone at 4 wk, which is, however, elevated at 16 wk. Other possible mechanisms that may contribute to the early fibrosis observed in this study can be related to the TGF-␤ and apoptosis pathways (17,27).…”
Section: Discussioncontrasting
confidence: 71%
“…Subsequent studies suggested that lower doses of eplerenone would be safe and sufficiently beneficial. We are conducting a double-blinded, randomized, placebo-controlled trial to evaluate the antialbuminuric effect of low dose of eplerenone (Eplerenone Combination Versus Conventional Agents to Lower Blood Pressure on Urinary Anti-albuminuric Treatment Effect Trial: EVALUATE) [89]. The study subjects will be 340 Japanese hypertensive patients with albuminuria receiving ACEIs or ARBs.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, EVALUATE (Eplerenone Combination Versus Conventional Agents to Lower Blood Pressure on Urinary Antialbuminuric Treatment Effect Trial) is ongoing as a placebo-controlled, double-blind trial to validate the additional effects of eplerenone on conventional therapies, primarily with RA inhibitors, in Japanese essentially hypertensive patients with albuminuria. 38 DM nephropathy patients and patients with an eGFR of o50 ml per minute per 1.73 m 2 for whom eplerenone is contraindicated were excluded from this trial. The result of this trial is expected to have a significant influence on the future treatment of CKD in Japan.…”
Section: Differentiation Of the Two Drugsmentioning
confidence: 99%